La representación de la espiritualidad mapuche en la música popular: el caso de Anklaje - Javier Silva-Zurita; Ignacio Soto-Silva; Leonardo Díaz-Collao (Resonancias, 2023)
Anklaje is a popular music group founded in the city of Castro in Chiloé Island, in southern Chile, whose creative work is characterized by the use of musical elements linked to the Mapuche Willliche people. In this article, we discuss how Anklaje represents Mapuche spirituality in its music, analyzing the interactions among territory, identity, and spirituality that articulate a particular creative process. We examine the band members’ discourses which characterize two ways of conceiving music practices, one linked to music as a rational expression and another as a spiritual experience. The results show how a construct of territory shapes a vision of spirituality, driving a representational practice based on the mediation between secular and sacred elements.